Craniofacial corrective surgery in Syndromic Craniosynostosis - Chi Adam, Khairul Bariah; Hariri, Firdaus; Lee, Chee Wei; Perumal, Kathivaran; Abdullah, Mohd Faizal; Berahim, Nazer (IntechOpen, 2021)
This surgical field has now progressed and becoming an established subspecialty involving various surgical disciplines worldwide. Various complex CMF syndromes reported in syndromic craniosynostosis include Crouzon, Apert and Pfeiffer syndromes. These syndromes carry specific functional discrepancies associated with the affected structural anomaly and may therefore have functional issues involving the brain, eye and airway among others. As corrective surgery is often indicated depending on the affected vital functions, other factors that need to be considered are patient’s age, comorbidities, urgency, available expertise and patient’s overall prognosis based on the degree of anomaly. As such, the corrective surgery can be categorized into; 1) intermediate which is performed at an early phase and aimed to improve or salvage important vital functions such as the brain, eye, airway or feeding which are important for the child’s development and, 2) definitive treatment aimed at permanently correct the functional discrepancies. Intermediate corrective surgery may include invasive procedures such as ventriculo-peritoneal (VP) shunts, tarsorrhaphy, adenotonsillectomy and tracheostomy whereas definitive corrective surgery may include surgical procedures such as monobloc, Le Fort III osteotomy, posterior cranial vault expansion and mandibular advancement. This chapter will elaborate on the indications, types, challenges in the management and the proposed prevention measures in corrective surgery for specifically for syndromic craniosynostosis patients.